Adipokine Signaling Pathways in Osteoarthritis - Zhang, Chaofan; Lin, Yunzhi; Yan, Chun Hoi; Zhang, Wenming (Frontiers in Bioengineering and Biotechnology, 2022)
Osteoarthritis (OA) is a debilitating joint disease that affects millions of individuals. The pathogenesis of OA has not been fully elucidated. Obesity is a well-recognized risk factor for OA. Multiple studies have demonstrated adipokines play a key role in obesity-induced OA. Increasing evidence show that various adipokines may significantly affect the development or clinical course of OA by regulating the pro/anti-inflammatory and anabolic/catabolic balance, matrix remodeling, chondrocyte apoptosis and autophagy, and subchondral bone sclerosis. Several signaling pathways are involved but still have not been systematically investigated. In this article, we review the cellular and molecular mechanisms of adipokines in OA, and highlight the possible signaling pathways. The review suggested adipokines play important roles in obesity-induced OA, and exert downstream function via the activation of various signaling pathways. In addition, some pharmaceuticals targeting these pathways have been applied into ongoing clinical trials and showed encouraging results. However, these signaling pathways are complex and converge into a common network with each other. In the future work, more research is warranted to further investigate how this network works. Moreover, more high quality randomised controlled trials are needed in order to investigate the therapeutic effects of pharmaceuticals against these pathways for the treatment of OA. This review may help researchers to better understand the pathogenesis of OA, so as to provide new insight for future clinical practices and translational research.